Exploring molecular mechanisms of exercise on metabolic syndrome: a bibliometric and visualization study using CiteSpace - Wan, Kang; Jin, Yue; Fan, Ruobing; Xu, Qizi; Li, Xiaoshi; Yan, Hongmei; Wang, Ru (Frontiers in Endocrinology, 2024)
Objective: To investigate the molecular mechanisms through which exercise influences metabolic syndrome (MS) and identify key research trends and collaborative networks using bibliometric and visualization techniques. Methods: We conducted a systematic literature search using the Web of Science Core Collection for articles published from 2014 to 2023. Using CiteSpace, we performed a bibliometric analysis of 562 eligible papers, generating visual knowledge maps to identify prevailing patterns, popular subjects, and emerging trends in the literature. Results: The study reveals that exercise mitigates MS by reversing high-fat diet-induced abdominal obesity, reducing lipid accumulation and inflammation, enhancing insulin sensitivity, and improving cardiovascular function. Key molecular pathways include PPAR-γ/CPT-1/MCAD signaling, AMPK activation, and nitric oxide production. The USA leads in research output, with significant contributions from American institutions. Collaboration among researchers is limited, highlighting the need for more extensive and high-quality research initiatives. Conclusions: Regular, moderate-to-high-intensity exercise is crucial for managing MS. Exercise activates beneficial molecular pathways, improving metabolic health and cardiovascular function. Future research should focus on expanding collaborations and exploring novel molecular targets to enhance the therapeutic potential of exercise in metabolic syndrome management.